The role of profit sharing in a dual labour market with flexible outsourcing - Erkki Koskela; Jan König (Center for Economic Studies and ifo Institute (CESifo), 2009)
We analyze the following questions associated with flexible outsourcing under partly imperfect dual domestic labour markets, where high skilled workers participate in firm's profit via profit sharing: How does the implementation of profit sharing influence flexible outsourcing? What is the relationship between outsourcing cost, profit sharing and wages? We show that profit sharing has a positive effect on low skilled wage and thus an outsourcing enhancing character. The wages of both types of labour are negatively correlated and lower outsourcing cost can increase the wage dispersion by decreasing the low skilled wage and raising the high skilled wage. The overall effect of profit sharing on high skilled wage is ambiguous due to a positive direct effect and a negative indirect effect via the low skilled wage.
Keywords: E23; E24; H22; J23; J51; J82; 330; Flexible outsourcing; dual labour market; profit sharing; labour market imperfection; employee effort; Outsourcing; Erfolgsbeteiligung; Dualer Arbeitsmarkt; Lohnstruktur; Theorie